Environmental exposures, sleep, physical activity, and risk of thyroid nodules in older adults: a cross-sectional study - Zhang, Jingbin; Zhao, Wenbo; Jin, Meichen; Wang, Wenping (Frontiers in Endocrinology, 2025)
BackgroundAs the global population ages, promoting healthy aging has become a critical public health priority. Emerging evidence suggests that environmental stressors—particularly residential noise—may influence endocrine health by disrupting behaviors essential to physiological homeostasis, such as sleep and physical activity.MethodsIn this cross-sectional study of 2,483 community-dwelling adults aged ≥60 years, we examined the associations between behavioral and environmental risk factors and the presence of thyroid nodules, assessed via standardized ultrasonography. Residential noise exposure was estimated using geospatial monitoring data. Sleep duration and quality, as well as physical activity levels, were collected through validated questionnaires. Poor sleep was defined as self-reported sleep duration of ≤6 hours and/or symptoms of disturbed sleep. Multivariable logistic regression models were used to estimate adjusted odds ratios (ORs) and 95% confidence intervals (CIs).ResultsPoor sleep (adjusted OR = 3.24; 95% CI: 2.70–3.90), low physical activity (adjusted OR = 2.51; 95% CI: 2.08–3.02), and high residential noise exposure (adjusted OR = 4.46; 95% CI: 3.70–5.39) were each significantly associated with the presence of thyroid nodules. Increasing age was also independently associated with higher risk. Mediation analyses indicated that sleep quality and physical activity jointly accounted for approximately 15–20% of the effect of noise exposure on thyroid nodule risk.ConclusionsBehavioral and environmental stressors, particularly poor sleep, physical inactivity, and noise exposure, may contribute to thyroid nodule formation in older adults. These findings highlight the importance of addressing modifiable behavioral pathways when evaluating environmental impacts on endocrine health.